The value of bond underwriter relationships - Stine Louise von Rüden; Jens Dick-Nielsen; Mads Stenbo Stenbo Nielsen (Danmarks Nationalbank, 2021)
We show that corporate bond issuers benefit from utilizing existing underwriter relationships when rolling over bonds, but at the same time become exposed to underwriter distress. A strong relationship enables the underwriter to credibly certify the issuer resulting in lower direct issuance costs and lower underpricing. However, if the underwriter becomes distressed, this spills over to the issuer's credit risk, because it weakens the relationship and increases the risk of involuntary relationship termination. The credit risk spillover is more pronounced for risky, information-sensitive issuers with high rollover exposure, i.e., those issuers most in need of certification by an underwriter.
Keywords: G12; G14; G21; G24; 330; Refinancing Risk; Credit Risk; Financial Stability